Characterization of Clostridioides difficile DSM 101085 with A−B−CDT+ Phenotype from a Late Recurrent Colonization. (17th April 2020) - Riedel, Thomas; Neumann-Schaal, Meina; Wittmann, Johannes; Schober, Isabel; Hofmann, Julia Danielle; Lu, Chia-Wen; Dannheim, Antonia; Zimmermann, Ortrud; Lochner, Matthias; Groß, Uwe; Overmann, Jörg
Abstract: During the last decades, hypervirulent strains of Clostridioides difficile with frequent disease recurrence and increased mortality appeared. Clostridioides difficile DSM 101085 was isolated from a patient who suffered from several recurrent infections and colonizations, likely contributing to a fatal outcome. Analysis of the toxin repertoire revealed the presence of a complete binary toxin locus and an atypical pathogenicity locus consisting of only a tcdA pseudogene and a disrupted tcdC gene sequence. The pathogenicity locus shows upstream a transposon and has been subject to homologous recombination or lateral gene transfer events. Matching the results of the genome analysis, neither TcdA nor TcdB production but the expression of cdtA and cdtB was detected. This highlights a potential role of the binary toxin C. difficile toxin in this recurrent colonization and possibly further in a host-dependent virulence. Compared with the C. difficile metabolic model strains DSM 28645 (630 Δerm ) and DSM 27147 (R20291), strain DSM 101085 showed a specific metabolic profile, featuring changes in the threonine degradation pathways and alterations in the central carbon metabolism. Moreover, products originating from Stickland pathways processing leucine, aromatic amino acids, and methionine were more abundant in strain DSM 101085, indicating a more efficient use of these substrates. The particular characteristics of strain C. difficile DSM 101085 may represent an adaptation to a low-protein diet in a patient with recurrent infections.